Nutritional status as predictor of quality of life in patients undergoing hemodialysis - Marina Abelha Barreto; Monica Cattafesta; Edson Theodoro dos Santos Neto; Luciane Bresciani Salaroli (Revista de Pesquisa Cuidado é Fundamental Online)
ABSTRACT